Role of glycogen and cellobiose PTS operon in Clostridiodes difficile virulence and pathogenesis - Hasan, Md Kamrul (Kansas State University, 2019)
Clostridiodes difficile, a Gram-positive, anaerobic bacterium, is the leading cause of antibiotic-associated nosocomial diarrhea in North America. C. difficile causes around half a million infections per year and costs about 4.8 billion dollars in healthcare bills. C. difficile’s major virulence factors are the extracellular toxins A and B. The disease is prevalent in the nosocomial environment and challenging to keep in check because of the highly resistant spores produced by the bacteria. Like many other pathogenic microbes, C. difficile virulence factors are strictly regulated in response to the nutrient availability to the cell. Glycogen is a storage carbon that many organisms use as a form of stored energy to use during the starvation condition. C. difficile genome harbors a glycogen biosynthesis operon, and we explored the role of glycogen in C. difficile growth and virulence by creating a mutant strain with a disrupted glgC gene of the operon. The resulting mutant was incapable of glycogen accumulation and produced very few spores, signifying glycogen is required for efficient sporulation in C. difficile. In correlation with glgC mutant’s higher toxin production and faster growth rate compared to its parent counterpart in in vitro condition, our animal infection model study showed that glycogen mutants are significantly more virulent in in vivo conditions. The second part of the thesis explores the role of cellobiose phosphoenolpyruvate:carbohydrate phosphotransferase system (PTS) operon in C. difficile virulence. In C. difficile, the cellobiose PTS operon is positioned from base 3287617 to 3291739 in the R20291 hypervirulent strain genome. The operon consists of 5 genes with putative functions of a PTS system and cellobiose catabolism. Cellobiose is a complex carbohydrate abundant in human gut originating from dietary cellulose and has documented role in many pathogens’ virulence. As such, we hypothesized that cellobiose metabolism plays a significant role in C. difficile virulence. CD2781 is a putative GntR class transcriptional regulator. Because of its immediate vicinity to the Cellobiose PTS operon and putative function we hypothesized that it is a regulator for Cellobiose PTS operon.
Keywords: Clostridiodes difficile; Glycogen; Cellobiose; Virulence; Pathogenesis